Association of tumor necrosis factor-alpha 308G/A polymorphism with recurrent miscarriages in women - Neha Sudhir; Badaruddoza; Archana Beri; Anupam Kaur (Wolters Kluwer Medknow Publications, 2016)
BACKGROUND: Recurrent miscarriage (RM) is the most common pregnancy loss in the first trimester affecting approximately 0.5-2% of women. It is a heterogeneous condition and remains an enigma as the underlying cause is still difficult to track down. AIM: This study was aimed to investigate the distribution of tumor necrosis factor-alpha (TNF-α) 308G/A polymorphism and its association with RM in females. The comparative picture was also demonstrated by comparing genotyping results with healthy control women having no history of miscarriage. METHODS: This clinical study was conducted among 115 women aged 21-44 years with history of recurrence of miscarriage. The samples were collected from women attending the outpatient departments of various hospitals, nursing homes, and infertility clinics of this region. In the present study, 111 fertile healthy women aged 24-46 years with at least one live birth and no history of miscarriage were also included. RESULTS: Mean age of women with RM was found to be 28 ± 5.6 years by recall method, whereas it was found to be 30 ± 7.4 in context to healthy women with no history of pregnancy loss. In the present study, 66% of women with RM had homozygous wild type genotype (GG) while 30% and 4% of women had heterozygous (GA) and homozygous mutant genotype (AA), respectively. Among control group, 79%, 16%, and 5% of women showed GG, GA, and AA genotype, respectively. CONCLUSION: The current study supports the concept of TNF-α 308G/A variant in particular with reproductive failure, GG and GA alleles showing 1-fold risk association with RM (odds ratio: 1.86 and 1.43, respectively).